Identification of (-)-Epigallocateshin gallate derivatives promoting innate immune activation via 2 ',3 '-cyclic GMP-AMP-stimulator of interferon genes pathway - Lee, Hyelim; Jeong, Jeong Hyun; Lee, Taegum; Chong, Youhoon; Choo, Hyunah; Lee, Sanghee (Pergamon Press Ltd., 2023)
(-)-Epigallocatehin-3-gallate (EGCG) is a catechin derived from green tea, which has been widely studied for its anti-oxidant and anti-tumor properties. Although EGCG plays important roles in various biological processes, the its effect on the immune system is not fully understood. In this study, we investigated the potential of EGCG as an activator of the stimulator of interferon genes (STING) pathway in the immune system. The cyclic GMP-AMP synthase (cGAS)-2-3-cyclic GMP-AMP (cGAMP)-STING pathway is crucial in the innate immune response to microbial infections, autoimmunity, and anticancer immunity. We confirmed that EGCG enhanced the immune response of cGAMP and identified E2 from 13 synthetic derivatives of EGCG. E2 specifically activated the interferon (IFN) signaling pathway specifically through STING- and cGAMP-dependent mechanisms. These results demonstrate the potential of EGCG and its derivatives as new STING activators that can stimulate the type I interferon response by boosting cGAMP-mediated STING activity.